APPLICABILITY OF CONTRARIAN INVESTMENT STRATEGIES IN SMALL CAPITALIZATION MARKETS: EVIDENCE FROM NASDAQ OMX VILNIUS - Paškevičius, Arvydas; Mickevičiūtė, Rūta (Ekonomika, 2011)
This study reviews previous research on the contrarian investment strategy as first analyzed by De Bondt and Thaler (1985), and aims at deepening and complementing the existing research on the subject. The paper analyses the results of applying the strategy to NASDAQ OMX Vilnius stocks over the period 2003–2010, dividing the testing into two groups: prior to the economic crisis and the crisis periods, based on the movement of the OMXV index. The method uses holding period returns in evaluating the standard contrarian investment strategy. The paper explains the methodology in detail and presents the findings which show no considerable holding period returns from the strategy in NASDAQ OMX Vilnius during the decline period; however, contrarian strategy seems to be a better option than a standard market index based portfolio during the periods of rapid growth when stocks are overrated.